The Complex Interplay Between Human Resource Management, Financial Literacy, and Management Accounting in Addressing Deviant Behavior and Fraud: A Systematic Literature Review - Soetikno, Johannes Johny (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This research explores the complex interplay between Human Resource Management (HRM), financial literacy, and management accounting in addressing deviant behavior and fraud within organizations. The primary aim of this study is to develop an integrated understanding of how these elements interact to prevent fraudulent activities and promote organizational integrity. Utilizing a systematic literature review approach, the research synthesizes findings from recent empirical studies and theoretical models, focusing on the last five years to provide a contemporary analysis The methodology involves a comprehensive review of relevant literature, assessing how various HRM practices, such as recruitment, training, and performance management, intersect with financial literacy and management accounting systems. The review reveals that an integrated approach, combining robust HRM practices with enhanced financial literacy and effective management accounting strategies, significantly contributes to reducing deviant behavior and mitigating fraud. Notably, HRM practices that emphasize ethical training and performance evaluations reinforce financial literacy among employees, which in turn strengthens their engagement with management accounting processes and internal controls. The results underscore the importance of adopting a holistic approach to fraud prevention. Organizations are encouraged to implement integrated training programs that combine financial literacy with ethical guidelines and performance management systems. This comprehensive strategy fosters a culture of transparency and accountability, thereby enhancing the overall effectiveness of internal controls and reducing the likelihood of fraudulent activities. The study contributes to the theoretical understanding of the interactions between HRM, financial literacy, and management accounting, providing practical insights for developing effective fraud prevention strategies.